2020
DOI: 10.1186/s12877-020-01525-8
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the relationships between different components of sarcopenia and brachial ankle pulse wave velocity in community-dwelling elderly

Abstract: Background: Previous studies have just found skeletal muscle mass decline is associated with arterial stiffness, but it is unclear whether muscle strength and physical performance as important compositions of sarcopenia are associated with arterial stiffness. The aim of this study was to investigate the relationship between sarcopenia, the components of sarcopenia and arterial stiffness among elderly in the community. Methods: This study enrolled 450 elderly people who received general medical examinations in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
(32 reference statements)
0
24
0
Order By: Relevance
“…In subjects with CVD or CVD risk factors ( Table 2 ), five out of seven studies found significant associations ( Watson et al, 2011 ; Ohara et al, 2015 ; Yamanashi et al, 2018 ; Rong et al, 2020 ; Zhang et al, 2021 ). For example, the study by Rong et al (2020) found that muscle strength as measured by handgrip dynamometer was negatively associated with baPWV in elderly subjects ( Rong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In subjects with CVD or CVD risk factors ( Table 2 ), five out of seven studies found significant associations ( Watson et al, 2011 ; Ohara et al, 2015 ; Yamanashi et al, 2018 ; Rong et al, 2020 ; Zhang et al, 2021 ). For example, the study by Rong et al (2020) found that muscle strength as measured by handgrip dynamometer was negatively associated with baPWV in elderly subjects ( Rong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In subjects with CVD or CVD risk factors ( Table 2 ), five out of seven studies found significant associations ( Watson et al, 2011 ; Ohara et al, 2015 ; Yamanashi et al, 2018 ; Rong et al, 2020 ; Zhang et al, 2021 ). For example, the study by Rong et al (2020) found that muscle strength as measured by handgrip dynamometer was negatively associated with baPWV in elderly subjects ( Rong et al, 2020 ). Whereas the study by Ohara et al (2015) found that muscle strength as measured by handgrip dynamometer was negatively associated with baPWV in middle-aged and older subjects ( Ohara et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, older adults tend to have poorer balance (King et al, 2016;Cruz-Jimenez, 2017), walk at slower speeds (Menz et al, 2003;Kim and Kim, 2014;Cruz-Jimenez, 2017), and take fewer steps per day (Bassett et al, 2010) than younger adults. These deficits continue to progress with further aging; endurance (Gardener et al, 2006;Schrack et al, 2016), walking speed (Xie et al, 2017;Morrison and Newell, 2019), balance (Xie et al, 2017), and muscle mass (Doherty, 2003;Castell et al, 2013;Rong et al, 2020) significantly decrease with increasing age from 50 to 80+ years old. Untreated, these impairments can lead to significantly reduced participation in the community (Allison et al, 2013;Warren et al, 2016) and an increased risk of falling (Verghese et al, 2009;Toebes et al, 2012;Ambrose et al, 2013;Lusardi et al, 2017), one of the leading causes of morbidity among older adults (Burns and Kakara, 2018).…”
Section: Introductionmentioning
confidence: 99%